Preclinical assessment of splicing modulation therapy for ABCA4 variant c.768G>T in Stargardt disease - Dyah W. Karjosukarso; Femke Bukkems; Lonneke Duijkers; Tomasz Z. Tomkiewicz; Julia Kiefmann; Andrei Sarlea; Sander Bervoets; Irene Vázquez-Domínguez; Laurie L. Molday; Robert S. Molday; Mihai G. Netea; Carel B. Hoyng; et al. (Communications Medicine)
Abstract Background Stargardt disease type 1 (STGD1) is a progressive retinal disorder caused by bi-allelic variants in the ABCA4 gene. A recurrent variant at the exon-intron junction of exon 6, c.768G>T, causes a 35-nt elongation of exon 6 that leads to premature termination of protein synthesis. Methods To correct this aberrant splicing, twenty-five 2′-O-methoxyethyl antisense oligonucleotides (AONs) were designed, spanning the entire exon elongation. Results Testing of these AONs in patient-derived photoreceptor precursor cells and retinal organoids allow the selection of a lead candidate AON (A7 21-mer) that rescues on average 52% and 50% expression of wild-type ABCA4 transcript and protein, respectively. In situ hybridization and probe-based ELISA demonstrate its distribution and stability in vitro and in vivo. No major safety concerns regarding off-targets, immunostimulation and toxicity are observed in transcriptomics analysis, cytokine stimulation assays in human primary immune cells, and cytotoxicity assays. Conclusions Additional optimization and in vivo studies will be performed to further investigate the lead candidate. Considering the high prevalence of this variant, a substantial number of patients are likely to benefit from a successful further development and implementation of this therapy.